Interdisciplinary nature of tactical and special training of cadets of educational organizations of the Ministry of Internal Affairs of Russia - Vyacheslav Vasilievich Batkhaev; Igor Anatolievich Kushnarenko (Вестник Майкопского государственного технологического университета, 2023)
An important factor in improving the professional training of personnel in the Russian Ministry Of Interior departmental university is the achievement of a high level of physical qualities, in particular strength, speed, coordination abilities, endurance and flexibility, which determine the success of the further formation of a rational technique of self-defense without weapons in hand-to-hand combat, as well as special tactical training (TST) and psychological readiness to serve in future law enforcement officers. The main importance in the tactical training of DIA officers is assigned to the educational organizations of the Russian Ministry Of Interior, where cadets receive training not only in physical, but also in tactical and special training, and in firepower training within the specially developed programs. During the TST cadets learn to act harmoniously in an emergency, adhere to a line of behavior that meets the requirements of the law, get acquainted with methods and tools that are effective in a difficult operational environment. The methodology of teaching TST includes not only theoretical, but also practical classes, which is due to the specifics of knowledge, skills and abilities transmitted in such classes, and the conditions of the operational environment in which cadets will have to apply this knowledge. The theoretical description of the content and directions of professional training of police officers (physical, technical, psychological) allows us to identify a characteristic feature of the general professional training of police officers, that is a close relationship between these areas of training. Key conclusions: The interdisciplinary connections of tactical and special training of cadets of educational organizations of the Ministry of Internal Affairs of Russia have been revealed. It has been shown that modern qualification requirements for a police officer can be implemented only as a systemic combination of parameters of tactical-special, fire, psychological and physical fitness.